Sodium-glucose co-transporter-2 inhibitors improve cardiovascular outcomes in heart failure with reduced ejection fraction regardless of ischemic etiology. (14th October 2021) - Patoulias, D; Boulmpou, A; Tsavousoglou, C; Toumpourleka, M; Siskos, F; Nikolaidis, A; Papadopoulos, C.E; Vassilikos, V; Doumas, M
Abstract: Background: Coronary artery disease remains the main underlying cause of heart failure (HF), despite the progress in prevention, diagnosis and treatment. Sodium-glucose co-transporter-2 inhibitors have been shown to improve surrogate cardiovascular outcomes in patients with HF with reduced ejection fraction (HFrEF), regardless of diabetes status. Purpose: We sought to determine the effect of SGLT-2 inhibitors on the primary composite endpoint (cardiovascular death or hospitalization for HF) across the two hallmark trials in the HFrEF population (EMPEROR Reduced and DAPA-HF), according to ischemic or non-ischemic etiology of HF. Methods: We pooled data from EMPEROR reduced and DAPA-HF trials in a total of 8, 474 patients with HFrEF, performing a sub-analysis according to the presence of ischemic cardiomyopathy as the underlying cause of HFrEF. Results: Treatment with SGLT-2 inhibitors resulted in a significant decrease in the risk for the primary composite outcome in patients with HFrEF of ischemic etiology, equal to 18% (RR=0.82, 95% CI: 0.73–0.92, I 2 =0%). In patients with HFrEF of non-ischemic etiology, SGLT-2 inhibitors produced a significant decrease in the risk for the primary composite outcome equal to 18% (RR=0.72, 95% CI: 0.63–0.82, I 2 =0%). Despite the greater effect in patients with non-ischemic HFrEF, no subgroup difference was detected (p=0.16). Generated results are summarized in Figure 1. Conclusions: SGLT-2 inhibitors improve surrogate cardiovascular outcomes both in patients with ischemic and non-ischemic HFrEF. Funding Acknowledgement: Type of funding sources: None.